EFFECT OF Averrhoa bilimbi L. A NATURAL DENTAL BLEACHING ON THE ROUHNESS OF NANOHYBRID COMPOSITE - Rahaju, Asih; Jeffrey; Igiola, Litanie (Fakultas Kedokteran Gigi Unjani, 2024)
Averrhoa bilimbi can be used as a natural tooth-bleaching ingredient because it can increase the brightness of tooth colour. In bleaching treatments, there are times when it is found that the patient's teeth have composite restorations. This study aims to determine the effect of Averrhoa bilimbi extract gel as a natural dental bleaching agent on the roughness of nanohybrid composites. The research method used 17 nanohybrid composite samples of 5 x 2 mm. Samples will be measured for surface roughness before treatment, and then samples will be applied with 50% Averrhoa bilimbi extract gel for 2 hours every day for up to 14 days and surface roughness test after treatment. The data were processed with t-test statistics; the statistical test results showed a p-value of 0.0001 (p<0.05), which means that the roughness value before and after 50% Averrhoa bilimbi extract gel treatment is a significant difference. It can be concluded that 50% of the Averrhoa bilimbi extract gel affects the roughness of nanohybrid composites. The average roughness value of the nanohybrid composite after 50% Averrhoa bilimbi extract gel treatment is 0.16 μm, which is still below the critical limit of roughness, so even though it is significant, 50% Averrhoa bilimbi extract gel can still be used safely as a natural tooth bleaching agent. DOI : 10.54052/jhds.v4n2.p137-146